Mapping the social side of pre-service teachers: connecting closeness, trust, and efficacy with performance - Liou, Yi-Hwa; Daly, Alan J.; Canrinus, Esther T.; Forbes, Cheryl A.; Moolenaar, Nienke M.; Cornelissen, Frank; Van Lare, Michelle; Hsiao, Joyce (Teachers and teaching, theory and practice, 2017)
This exploratory study foregrounds the important, but often understudied social side of pre-service teacher development and its relation to teaching performance in one university-based teacher preparation program in the US. We examine the extent to which pre-service elementary teachers' social relationships and perceptions of peer trust and efficacy are associated with performance on a high stakes mathematics teaching assessment. Findings suggest that social and emotional support through close social ties, peer trust, and self-efficacy are significantly and positively associated with pre-service teachers' teaching performance. Our work further contributes to the development and discourse about teacher education in university-based teacher preparation programs.